Power converter for battery charger of electric vehicle with controllable charging current - Suroso, Suroso; Prasetijo, Hari; Winasis, Winasis; Siswantoro, Hari; Nugroho, Daru Tri; Utomo, Wahyu Mulyo; Abu Bakar, Afarulrazi (Institute of Advanced Engineering and Science, 2024)
Research on electric vehicle chargers primarily focuses on improving charging technology to enhance the convenience, quality, efficiency, and affordability of charging electric vehicles. This paper discusses a different AC-DC power converter topology proposed as a potential candidate for electric vehicle battery charger. Using the proposed converter circuit, the charging process of electric vehicle battery can be simply adjusted to meet the battery requirement, and even for increasing the charging speed while avoiding overcharging of battery. During the charging process, if the voltage of battery approaches to the targeted battery voltage level, the charging current can be reduced gradually to zero. Hence it will prevent the battery from overcharging condition. Moreover, the ability of working at high power factor operation, low distortion of alternating current (AC) input current, and low direct current (DC) output current ripple are other features of the proposed charger circuits. Some test results of the proposed power converter were presented. The test results revealed potential features of the converter for battery charger of electric vehicle with power factor 0.9996, total harmonic distortion (THD) of AC current 2.73%, and low charging current ripple, i.e. 3.91%. Therefore, it minimizes the negative effects caused by ripples of charging current especially for lithium-ion batteries widely used in electric vehicles.